العراقية Bos indicus والأبقار Camelus dromedariues دراسة نسجية مقارنة لكبد الإبل - ضمياء قاسم سكر; هيفاء عبد علي الشمري; طه جاسم الطه (University of Thi-Qar Journal of Science, 2019)
The camel liver is highly lubulation in comparative with liver cows , so this study show highlysignificant difference between the two species in the size of the hepatocytes and their nuclei . thehepatocytes & nucleus in camel liver is very polyhedrale and large than that in cow liver which ismore arrange .the diameter of sinusoid in cow liver is larger than that in camel